2013
DOI: 10.1158/1078-0432.ccr-13-0380
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Transfer of Tumor-Infiltrating Lymphocytes in Patients with Metastatic Melanoma: Intent-to-Treat Analysis and Efficacy after Failure to Prior Immunotherapies

Abstract: Purpose: Adoptive cell transfer (ACT) using autologous tumor-infiltrating lymphocytes (TIL) was reported to yield objective responses in about 50% of metastatic patients with melanoma. Here, we present the intent-to-treat analysis of TIL ACT and analyze parameters predictive to response as well as the impact of other immunotherapies.Experimental Design: Eighty patients with stage IV melanoma were enrolled, of which 57 were treated with unselected/young TIL and high-dose interleukin-2 (IL-2) following nonmyeloa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
279
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(306 citation statements)
references
References 26 publications
16
279
2
2
Order By: Relevance
“…Recent clinical trials have shown that adoptively transferred T cells generated with different approaches can induce clinically relevant responses for a variety of malignancies (4)(5)(6)(7)(8)(9)(10)(11). However, although some of the patients can achieve complete eradication of the tumors, many of the patients with partial responses eventually relapse (4,5,7,12,13). The data from these clinical trials have suggested that persistence of the transferred T cells is highly correlated with treatment outcome (5,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical trials have shown that adoptively transferred T cells generated with different approaches can induce clinically relevant responses for a variety of malignancies (4)(5)(6)(7)(8)(9)(10)(11). However, although some of the patients can achieve complete eradication of the tumors, many of the patients with partial responses eventually relapse (4,5,7,12,13). The data from these clinical trials have suggested that persistence of the transferred T cells is highly correlated with treatment outcome (5,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach that has been used recently is to perform adoptive T-cell therapy (ACT), in which tumor-infiltrating lymphocytes (TIL) are isolated from metastases in patients, massively expanded in vitro, and transferred back into patients. Clinical trials have revealed great efficacy of ACT with an objective response rate of about 40% to 50% and a complete response rate of about 10% to 20% (18)(19)(20)(21)(22). However, the process for generating a large number of TILs can be complex and time consuming; as a result, a high percentage of patients have to drop out during TIL preparation.…”
Section: Introductionmentioning
confidence: 99%
“…A GMP-compliant TIL production process has been established in Manchester in partnership with colleagues at the NKI, Amsterdam; Herlev Hospital, Copenhagen; and the Sheba Medical Centre, Israel, based upon studies carried out at the National Cancer Institute, Bethesda, MD. 3,4 Currently, seven patients have received melanoma TIL outside of the clinical trial situation under a ''specials'' protocol where patients are treated on a compassionate-use basis. A phase II study funded by the NIHR Efficacy and Mechanism Evaluation (EME) program comparing high-and low-dose IL-2 cytokine support in malignant melanoma patients receiving TIL (METILDA) is currently on-hold because of NHS budget issues.…”
Section: Christie Hospital and The University Of Manchestermentioning
confidence: 99%
“…Ex vivo expansion in a cocktail of various cytokines may reverse the functional deficit before reinfusion. Reports of objective clinical responses in 50-70% of patients with advanced chemoresistant melanoma after TIL therapy 3,4 suggest that this hypothesis has been proven. The long-term goal in this area now becomes to make TIL therapy practical and the antitumor effect durable.…”
Section: Introductionmentioning
confidence: 99%